Contagion and Volatility with Imperfect Credit Markets - Aizenman, Joshua (IMF Working Papers; Working Paper, 1997)
This paper interprets contagion effects as an increase in the volatility of aggregate shocks impinging on the domestic economy. The implications of this approach are analyzed in a model with two types of credit market imperfections: domestic banks borrow at a premium on world capital markets, and domestic producers (whose demand for credit results from working capital needs) borrow at a premium from domestic banks. Higher volatility of producers' productivity shocks increases both domestic and foreign financial spreads and the producers' cost of capital, resulting in lower employment and higher incidence of default. Welfare effects are nonlinearly related to the degree of international financial integration.